A Coupled FEM-BEM Approach for the Solution of the Free-Boundary Axi-Symmetric Plasma Equilibrium Problem (Communications in Computational Physics, 2021)
In this paper we present a coupled Finite Element Method – Boundary Element Method (FEM-BEM) approach for the solution of the free-boundary axi-symmetricplasma equilibrium problem. The proposed method, obtained from an improvementof the Hagenow-Lackner coupling method, allows to efficiently model the equilibriumproblem in unbounded domains by discretizing only the plasma region; the externalconductors can be modelled either as 2D or 3D models, according to the problem of interest. The paper explores different iterative methods for the solution of the nonlinearGrad-Shafranov equation, such as Picard, Newton-Raphson and Newton-Krylov, in order to provide a robust and reliable tool, able to handle large-scale problems (e.g. highresolution equilibria). This method has been implemented in the FRIDA code (FRee-boundary Integro-Differential Axisimmetric – https://github.om/matteobonotto/FRIDA), together with a suitable Adaptive Integration Technique (AIT) for the computation of the source term. FRIDA has been successfully tested and validated againstexperimental data from RFX-mod device, and numerical equilibria of an ITER-like device.